Level of knowledge on wasiyyah: a study at Kampung Ganchong Tengah Pekan Pahang / Mohd Syafiq Mohd Ayob - Mohd Ayob, Mohd Syafiq (2019)
Wasiyyah or will in one of the issues faced by Malaysian especially Malay society. Awareness to make wasiyyah among Malay society is still low compared to non- Muslims. This is because of the perceptions of Malay society that the distribution of inheritance through faraid is sufficient. So in this research, the researcher was chosen the specific place which is Kampung Ganchong Tengah Pekan Pahang. This research to study the level of knowledge on wasiyyah among the people at Kampung Ganchong Tengah Pekan Pahang. The independent variables in this study are information, level of understanding and importance of wasiyyah. The study will use primary data which data will be collected through the distribution of questionnaires and it will analyze by SPSS using descriptive analysis and Pearson correlation. The study also using the qualitative method by interviewing several people to get information about wasiyyah.